Wealth-related inequalities in adoption of drought-tolerant maize and conservation agriculture in Zimbabwe - Makate, C.; Makate, Marshall; Mango, N. (2019)
© 2019, International Society for Plant Pathology and Springer Nature B.V. This paper concerns Drought-Tolerant Maize (DTM) and Conservation Agriculture (CA) practices that were introduced into smallholder maize-based farming systems in Zimbabwe to enhance the productivity of maize and food security under a changing climate. Although these technologies are technically appropriate, there are difficulties with their use by smallholder farmers of relatively low socio-economic status, as measured through ownership of farm or household assets and endowments. Thus, we sought to quantify and explain wealth-related inequalities in the adoption of DTM and CA in smallholder farming communities and discuss their implications for food security. The analysis used cross-sectional household-level data gathered from 601 smallholder farmers from four districts in Zimbabwe. We found evidence of a pro-rich distribution of inequalities in the adoption of DTM and CA that were mostly explained by differences in household wealth, access to agricultural extension services and size of farm land. No meaningful differences in DTM adoption disparities were found across districts. Significant gender differences were observed for CA, and meaningful differences by district were noted. Results suggest the need for decision makers to consider implementing policies that focus on the poorer segments of the farming society to alleviate differences in the adoption of such agricultural technologies. For example, subsidizing the uptake of improved maize varieties including DTM and prioritizing equitable land distribution, coupled with specialised extension services for the poor in a cereal-based CA farming system, could reduce the observed gap between rich and poor in the uptake of these innovations and consequently improve food security.